Controlled thickness and morphology for highly efficient inverted planar heterojunction perovskite solar cells1. Issue 24 (28th June 2015) - Xi, Jun; Wu, Zhaoxin; Dong, Hua; Xia, Bin; Yuan, Fang; Jiao, Bo; Xiao, Lixin; Gong, Qihang; Hou, Xun
<x xml:space="preserve">Abstract</x> Recently, inverted planar heterojunction (PHJ) perovskite solar cells have been developed rapidly by numerous preparations and relative optimizations.